Comparison of the Intestinal Microbiota Composition and Function of Red Claw Crayfish (Cherax quadricarinatus) Cultured in Ponds and Rice Fields - Libin Huang; Tianhe Lu; Xiaohua Lu; Jingu Shi; Yin Huang; Xuesong Du; Dapeng Wang; Yi Liang; Yanju Lei; Lianggang Wang; Rui Wang; Huizan Yang (Fishes)
The growth environment significantly influences the intestinal microbiota of aquatic organisms. We investigated the composition and functional differences in the intestinal microbiota of red claw crayfish (Cherax quadricarinatus) in rice fields (RB) and ponds (PB) by 16S rDNA high-throughput sequencing technology. The results indicate that the Shannon, Simpson, Sobs, Chao1, and ACE indices of PB are all higher than those of RB, demonstrating greater diversity and richness of intestinal microbiota. The dominant phyla in the intestinal microbiota of the Cherax quadricarinatus were Proteobacteria, Tenericutes, and Firmicutes. Tenericutes and Proteobacteria were significantly more abundant in the RB than in the PB, while Planctomycetes and Firmicutes were significantly more abundant in the PB than in the RB. The results of network correlation analysis indicate that Proteobacteria and Firmicutes exhibit strong connectivity with other microbial groups in the gut microbiota of Cherax quadricarinatus, showing significant centrality. They play an important role in the interactions within the gut microbiota community. The dominant bacterial genera in the Cherax quadricarinatus’s gut were Citrobacter, Candidatus_Bacilloplasma, and Clostridium_sensu_stricto_1. The abundance of the genus Clostridium was significantly higher in the PB than in the RB, whereas the abundance of Candidatus_Hepatoplasma and Vibrio was significantly lower in the PB than in the RB. The prediction function of KEGG enrichment showed that the abundance of Amino acid metabolism, Biosynthesis of Other Secondary Metabolites, Transport and Catabolism, Cancers, and Nervous System, Substance Dependence were significantly higher in the PB, while the infectious diseases pathway was enriched in the RB. In summary, our results revealed significant differences in the composition and diversity of intestinal microbiota in the Cherax quadricarinatus between rice paddy and pond farming environments. The intestinal microbiota of the Cherax quadricarinatus grown in pond environments exhibit higher diversity and stability, manifested by an increase in beneficial bacteria abundance and a decrease in opportunistic pathogens. These findings significantly improve understanding of the complex relationship among Cherax quadricarinatus, intestinal microbiota, and the environment.